EFFICACY OF ETANERCEPT IN PATIENTS WITH RHEUMATOID ARTHRITIS (results of the Russian multicenter ETALON study) - Anna Olegovna Pchelintseva; E Yu Panasyuk; O F Ryabitseva; V I Mazurov; I G Salikhov; A E Sizikov; O N Ivanova; V N Sorotskaya; O V Semagina; I V Vinogradova; A I Kulikov; L N Denisov; et al. (Научно-практическая ревматология)
Objective. To evaluate the effectiveness and tolerance of Etanercept (ETN) therapy in patients with rheumatoid arthritis (RA).Material and Methods. 188 adult patients with severe and moderate RA (average DAS28 score of 6.26±0.89) subcutaneously received 50 mg/wk ETC during 24 wk along with therapy using disease-modifying antirheumatic drugs (DMARDs). The effectiveness was assessed using the EULAR and ACR20/50/70 criteria, dynamics of HAQ, SDAI, CDAI, ESR, and the C-reactive protein level.Results. By the end of the study, low activity of the disease according to EULAR (DAS28 score ≤ 3.2) was achieved in 31.9% of patients; remission (DAS28 score ≤ 2.6) was achieved in 17% of patients. ACR20/50/70 response was achieved in 72.3; 47.8 and 20.2% of patients, respectively. A decrease in the HAQ index by at least 0.25 points was achieved in 67.5% of patients. The overall EULAR response (moderate and good) was observed in 79.3% of patients; SDAI and CDAI remission/low activity was observed in 52.3 and 52.7% of patients, respectively. Some patients achieved clinical response only by the 25th week of treatment. The originally moderate RA activity and administration of methotrexate are the factors determining higher ETN effectivity in RA patients. The general tolerance of ETN was satisfactory; no uncommon adverse effects were observed.Conclusions. Analysis of the results of ETN therapy for 6 months attests to high effectiveness of this drug. Its advantages include the rapid clinical effect in most patients and good tolerance. ETN can be recommended for treatment of patients with moderate and severe RA when the conventional DMARDs therapy turns out to be insufficiently effective.